2009
DOI: 10.1002/anie.200903360
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Acid Catalysis in Reactions of Peroxyl Radicals with Phenols

Abstract: Weak organic acids in millimolar concentrations increase the reactivity of peroxyl radicals with common phenolic antioxidants dramatically. This counterintuitive phenomenon relies on a substantially different reaction mechanism from that in the absence of an acid: rate‐determining electron transfer occurs from the hydrogen‐bonded phenol to the hydroperoxide cation radical present in equilibrium with the peroxyl radical under these conditions (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 27 publications
7
74
0
Order By: Relevance
“…50 Consistent with this small α 2 H value, the reactivity of Fer-1 and Lip-1 toward peroxyl radicals differed only by factors of 1.7 and 0.6 when measured in DMSO (an excellent H-bond accepting solvent) compared to chlorobenzene (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 58%
“…50 Consistent with this small α 2 H value, the reactivity of Fer-1 and Lip-1 toward peroxyl radicals differed only by factors of 1.7 and 0.6 when measured in DMSO (an excellent H-bond accepting solvent) compared to chlorobenzene (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 58%
“…92 The phenomenon was shown to be general for half a dozen common phenolic antioxidants and both organic and mineral acids. The rate acceleration increases with the concentration of acid, but not the acid strength; it is largest for carboxylic acids, and requires a relatively polar solvent such as acetonitrile to be effective.…”
Section: Dpphmentioning
confidence: 99%
“…Mechanistic studies support a H-atom transfer mechanism as for phenols (k H /k D ∼ 3), 64,106 a negative reaction constant for Hammett-type correlation with σ + , 107,165 HBA solvents slow kinetics, 64,106,166 and theoretical calculations yield transition states consistent with a role for PCET in this process. 92 This development has prompted the study of lipid-soluble analogs of pyridinol 65 (which has the best balance of reactivity to peroxyl radicals and stability in air, and most closely resembles α-TOH) under more physiologically relevant conditions, for 80 Since the peroxidation of membrane lipids has been implicated in virtually all degenerative diseases, the potential for these compounds to…”
Section: Ho N H 62mentioning
confidence: 99%
“…[8] We have recently shown that their reactions are acceleratedi np olar organic solvents( MeCN or EtCN) containing protic acids, in which it was suggested that the reactions proceed by as tepwise mechanism involving rate-controlling ET to the protonated peroxyl radical. [11] Litwinienko and Ingold and also Foti and co-workersi ndependently showed that, in alcohols, acidic phenols are oxidisedb yt he 2,2-diphenylpicrylhydrazyl radical (DPPHC)a tamuch faster rate than expectedf rom an EPT (CPET), following as tepwise PT-ET pathwayn amed sequential protonl oss electron transfer (SPLET), which involves the solvent as proton acceptor. [12] The key role of the solvent as proton acceptor was also highlighted by SavØant and co-workersi nt he electrochemical oxidationo f phenolsinwater,although they described it as aCPET.…”
Section: Introductionmentioning
confidence: 99%